2017
DOI: 10.1097/gox.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Prepectoral and Subpectoral Expander-Based Breast Reconstruction and Clavien IIIb Score Outcomes

Abstract: Background:Prepectoral breast reconstruction is increasingly popular. This study compares complications between 2 subpectoral and 1 prepectoral breast reconstruction technique.Methods:Between 2008 and 2015, 294 two-staged expander breast reconstructions in 213 patients were performed with 1 of 3 surgical techniques: (1) Prepectoral, (2) subpectoral with acellular dermal matrix (ADM) sling (“Classic”), or (3) subpectoral/subserratus expander placement without ADM (“No ADM”). Demographics, comorbidities, radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 45 publications
(26 reference statements)
10
62
1
Order By: Relevance
“…In fact, Nahabedian reported very high infection rates (12.8% by patient; 8.1% by breast) not in line with iBAG study outcomes, while implant loss rate was similar (6.5%) and slightly different necrosis and seroma rates (9.7% and 4.8%) 17 . High implant and expander loss rate, as well as infection one, were also found in Bettinger and Schnarrs publications about prepectoral expander/implant reconstructions, with overall infection rates of 9.1% for the first one and 11.8% for the second, reinforcing again our hypothesis 20,21 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, Nahabedian reported very high infection rates (12.8% by patient; 8.1% by breast) not in line with iBAG study outcomes, while implant loss rate was similar (6.5%) and slightly different necrosis and seroma rates (9.7% and 4.8%) 17 . High implant and expander loss rate, as well as infection one, were also found in Bettinger and Schnarrs publications about prepectoral expander/implant reconstructions, with overall infection rates of 9.1% for the first one and 11.8% for the second, reinforcing again our hypothesis 20,21 …”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, patient's risk factors revealed by our statistical analysis find confirmations in other publications: Schnarrs highlighted higher postoperative complications risk in smokers and patients with >500 g breasts, 20 while Bettinger observed increased complication rates in previously irradiated breasts and no significant association between chemotherapy and postoperative adverse events 21 …”
Section: Discussionsupporting
confidence: 85%
“…Recently, the long-term results of clinical studies on the pre-pectoral reconstructions by means of a synthetic matrix were published (11,12). Several other studies reported similar results with biological matrixes (8,(13)(14)(15)(16)(17)(18)(19). A pre-pectoral approach showed, in all these series, a highly documented surgical safety, comparable to the standard full muscular coverage and to the dual-plane coverage.…”
Section: Surgical Techniquesupporting
confidence: 54%
“…This is in contrast to the results of some studies, which reported no significant difference between the two. [15][16][17] The notable difference in complication rates between sub-or prepectoral implant-based breast reconstruction may be attributed to the less invasive operative technique used in prepectoral implant-based breast reconstruction, which may also partially explain its increasing popularity.…”
Section: Discussionmentioning
confidence: 99%